Das praças para as urnas: movimentos dos Indignados e Occupy Wall Street | From squares to ballot: “Indignados” movement and Occupy Wall Street - Tostes, Ana Paula Balthazar; Barros Silva, Lucca Viersa (Mural Internacional, 2016)
Após um longo período em que movimentos sociais pareciam estar em retração, desde o fim do ano de 2010 as sociedades civis em diversos países, com focos e dinâmicas diferentes, foram para as ruas. Neste artigo analisa-se dois movimentos advindos desse período de protestos, o Occupy Wall Street ocorrido nos Estados Unidos, e o movimentos dos Indignados (ou Movimento 15M) na Espanha. O objetivo desse artigo é contribuir para reflexão sobre as trajetórias distintas, mas em certa medida bem-sucedidas de dois movimentos sociais anti sistêmicos. Primeiro, o Movimento dos Indignados na Espanha, que se organizou e se institucionalizou, dando origem ao partido político Podemos. Segundo, o Occupy Wall Street, que não se desdobrou em um novo partido político, no entanto pode ser atribuído em parte à força política do senador Bernie Sanders nas eleições primarias do partido Democrata nos Estados Unidos em 2016. ABSTRACT After a long period in which social movements seemed to be in retraction, since 2010 civil societies in many countries, with different focuses and dynamics, took the streets. Since the Arab Spring events until the manifestations in the US, Spain and even later in Brazil drove social scientists to continue with the social movements theme in search for the attempt to understand the protest and nonpartisan popular manifestations' reasons, impacts, differences and dynamics that took place over these years. This article analyzes two movements derived from this protest period, the Occupy Wall Street which happened in the US, and the “Indignados” movement (or 15M movement) in Spain. This article's goal is to contribute to the reflexion on the distinct path, but in a certain way well-succeeded of two anti-systemic movements that became popular, in particular from 2013. First, the “Indiganados” movement in Spain, which got organized and institucionalyzed and gave rise to the political party Podemos. Second, Occupy Wall Street, which didn't unfold into a new political party, but can be partially attributed to Bernie Sanders political strenght in the presidential primary elections of the Democratic party in the US in 2016. Palavras-chave: movimentos sociais; Occupy; Indignados; 15M; Podemos, eleições nos EUA Keywords: social movements; Occupy; Indignados; 15M; Podemos; elections in US DOI: 10.12957/rmi.2015.23761 Recebido em 15 de Janeiro de 2016 | Received on January 15, 2016 Aceito e, 28 de Janeiro de 2016 | Accepted January 28, 2016.